Determining the Mechanism of Trade Exchange in America and China - . Jabbar, Abduljabbar Hani A (Opción)
Determine the nature of Supply and demand for each currency of the two countries, So the side of the money supply is a constant that is determined by the policy of the central bank in each country that responds to market changes in addition to its predetermined goals either side Demand depends on consumer decisions to invest in business units and individuals I each country in the currency of the other country (Hussein 2018). The rise in the price of the dollar against the yen from 6.5 yen per dollar to 7.15 yen per dollar will reduce the desire of Chinese individuals or investors to import American goods at the Same Time, the desire of in individuals America to import Chinese goods increases by the amount related to the exchanges rate of each currency and this leads to an increase in the money supply of the dollar in America in response to the desires of the American individuals. determine the nature of Supply and demand for each currency of the two countries, So the side of the money supply is a constant that is determined by the policy of the central bank in each country that responds to market changes in addition to its predetermined goals either side Demand depends on consumer decisions to invest in business units and individuals I each country in the currency of the other country (Hussein 2018). The rise in the price of the dollar against the yen from 6.5 yen per dollar to 7.15 yen per dollar will reduce the desire of Chinese individuals or investors to import American goods at the Same Time, the desire of in individuals America to import Chinese goods increases by the amount related to the exchanges rate of each currency and this leads to an increase in the money supply of the dollar in America in response to the desires of the American individuals